AGUA DE MAR CRUDA PARA LAS ZONAS URBANAS PRÓXIMAS AL MAR - Gonzales Cotillo, Mario (2007)
From the distribution of the consumption of water from the urban areas, 28% corresponds to toilets. The total minimum amount of consumption of water according to SUNASS is 10 liters per inhabitant; hence, 50 liters correspond to daily water discharged from toilets. The volume of tap water going to toilets is elevated, but it becomes worst if we have in mind that more than millions of peruvians do not have access to this natural resource and that 4500 children die daily because of this deficiency. There is an idea that part of this huge volume of tap water that is being used for toilets would be replace with filtered sea water; for that reason, seven districts with significant population from Lima and Callao were selected for this experiment because of their proximity to the sea. The conclusion after the analysis experimenting tap water being replaced by filtered sea water only in districts selected, can make us conserve more than 102 millions liters of tap water daily, and this amount would be useful for almost 00,000 inhabitants.